Biomass production and salt extraction by species alone or associated in the revegetation strategy - Camila Barros Silva Leite, Maria (Revista Ciência Agronômica, 2021)
Anthropogenic actions have caused soil degradation and revegetation is a way to recover degraded soils. However, salt-affectedsoils require the use of suitable species to extract salts from the soil. This study investigated the growth of shrub and tree species in a soil degradedby salts, alone or associated with a phytoextraction salt species, evaluating plant biomass yield and extraction of elements by plants. A fieldexperiment was assembled with eight treatments: 1) Atriplex nummularia Lindl., 2) Mimosa caesalpiniifolia Benth, 3) Leucaena leucocephala(Lam.) Wit, 4) Azadirachta indica A. Juss, 5) A. nummularia + M. caesalpiniifolia, 6) A. nummularia + L. leucocephala and 7) A.nummularia + A. indica; in randomized blocks with four replications. After 30 months of cultivation, plants were collected to measurebiomass and concentrations of Na, K, Ca, Mg, Cl, P, and N. A. indica plants had the highest total biomass (10.75 kg plant-1), about 15times more than M. caesalpiniifolia, both in associated cultivation with A. nummularia. A. nummularia plants extracted more Na and Clin the dry matter, maximum of 124.70 and 166.79 g plant-1, respectively. The highest production of plant biomass (23.55 t ha-1) and totalextraction of elements (1438.51 kg ha-1) were obtained by associated cultivation of A. nummularia and A. indica. Associated cultivation didnot decrease the phytoextractor potential of Na and Cl by A. nummularia plants and it can be used to regenerate degraded areas.